PENINGKATAN KEMAMPUAN ANTIOKSIDAN PADA KRIM KULIT JERUK NIPIS (Citrus aurantifolia S) MENGGUNAKAN VCO DENGAN METODE DPPH - Dyani Primasari Sukamdi; Sabtanti Harimurti; Kunniya Amany; Vella Lailli Damarwati (JCPS (Journal of Current Pharmaceutical Sciences), 2024)
Lime peel (Citrus aurantifolia S.) is rich in flavonoids, tannins, and coumarins so that it can act as an antioxidant. It can be formulated with Virgin Coconut Oil (VCO) into a cream to protect the skin and prevent aging. This study aims to determine the antioxidant activity of cream preparations containing lime peel extract with DPPH method and to determine whether the concentration of VCO can affect the physical evaluation and antioxidant activity of cream preparations. Lime peel was extracted by maceration method using 96% ethanol and cream were made using various VCO concentrations (30%, 35% and 40%). The three formulas were physically tested to determine the effect of adding VCO concentration to the physical quality of the cream. Data analysis was carried out using the One-Way Anova method and the results of the adhesive power test, dispersion and pH concluded that the significance was, therefore the addition of VCO concentration does not affect the value on adhesion, spread ability and pH. The IC50 results obtained for formulas I, II and III are 31.78 ppm, respectively; 29.64 ppm ; 26.95 ppm. Data was statistically tested using One-Way Anova, the results showed that lime peel extract cream with the addition of VCO affected antioxidant activity in cream preparations. Where the greater the concentration of VCO used in lime peel cream, the greater the antioxidant activity. Keywords : Lime peel, cream, extract, VCO, antioxidants